Oxygen consumption in the sandy beaches of the Vistula River: Goods and services of the ecosystem - Słodownik, Patrycja; Opaliński, Krzysztof W. (Studia Ecologiae et Bioethicae, 2012)
Oxygen consumption in the sandy beaches of the Vistula River: Goods and services of the ecosystem The aim of the research was to estimate the role of the beach in the process of self – purification of water in the Vistula River. The study could become a very important voice in the debate about the future and development of Vistula River. A self-purification process involves the disposal of pollutants entering the water from the catchement of the River. A measure of the Vistula water purification process of organic matter is the amount of oxygen that is consumed by the beach settlement. That is the amount of burned organic matter by psammon during cellular respiration. In addition, the calculation of the amount of organic matter, which was worn by psammon can be the measure of “goods and services of the ecosystem” of the river.